Biomagnification of mercury in an Antarctic marine coastal food web - BARGAGLI, R.; MONACI, F.; SANCHEZ-HERNANDEZ, J. C.; CATENI, D. (Marine Ecology Progress Series, 1998)
Total Hg concentrations were determined in marine sediments and biota from the inner shelf of Terra Nova Bay (Antarctica). Like published data on air, snow and soils from the same region, Hg levels in the finest fraction of marine sediments were among the lowest ever reported for coastal marine environments (0.012 ± 0.007 μg g-1 dry wt). A progressive increase in Hg concentrations was found in organisms at different levels of the marine food web (phytoplankton < zooplankton and benthic primary consumers < detritivorous and opportunistic benthic invertebrates < epipelagic fish < demersal fish and plankton-feeding seabirds < fish-eating penguins < predatory birds and Weddell seal). In general, primary producers and consumers showed slightly lower Hg concentrations (0.076 ± 0.023 μg g-1 dry wt) than organisms of related species from other seas, but values in feathers (2.91 ± 1.93 μg g-1 dry wt) of the Antarctic skua and in tissues of a Weddell seal (44.0 and 24.0 μg g-1 dry wt in the liver and spleen, respectively) were similar to those in skuas and seals from the northern hemisphere. Trophic connections between organisms in well developed benthic communities, phytoplankton and fish and environmental factors such as enhanced upwelling of cold water, sea ice and low light are deemed to enhance natural biomagnification processes of Hg in the pristine Antarctic coastal environment.